Respuesta :

Answer: a. (2,3)

Step-by-step explanation: y=-1.5x+6--(1)

                                             y=x+1--(2)

                                             Sub y=x+1 into (1)

                                             x+1=-1.5x+6

                                             2.5x=5

                                             x=2

                                             Sub x=2 into (2)

                                             y=3

msm555

a. (2,3)

Answer:

Solution Given:

y= -1.5x+6........[1]

y=x+1.................[2]

Now solving equation 1 and 2 we get

-1.5x+6=x+1

6-1=x+1.5x

2.5x=5

x=5/2.5

x=2

again

substituting value of x in equation 2, we get

y=2+1=3

so

solution(x,y)=(2,3)

Step-by-step explanation: